The Transcultural Generation Narrative: A Comparison of German and French Literary Generations after World War I (KULT_online, 2012)
In his comprehensive and comparative study of two putative generations of authors, namely the French group Inquiétude and the German post-war generation, Ralph Winter focuses on the generational self-interpretation of both generations. Analysing the commonalities of the generational contexts as well as their public self-thematization, Winter successfully argues for the transcultural phenomenon of the 'generation narratives' to be a strategy for positioning the authors in a literary field. Although the historical, discursive, and experiential commonalities of the groups suggest them to be distinct generationalities, Winter shows the term 'generation' to be strategically used in order to establish the young authors as serious writers. By means of the successful combination of a generation studies' approach with Bourdieu's theory of the literary field, Generation als Strategie (Generation as Strategy) critically examines the concept 'generation' and makes a pivotal contribution to the study of processes of communitarisation in the literary field.